Wireless pointing device using capacitive coupling - Abdul Rahman, Abdul Wahab; Tan, Eng Chong; Low, Kay Min (1997)
Increasing demand and use of computers prompted extensive studies on implementing low cost and reliable pointing devices. The use of the capacitive coupling technology allows wireless polinting devices to be reliable and do not require any battery. The proposed pointing device uses the capacitive coupling technology to detect both the x and y position of the mouse/digitizer and also if any of the buttons were pressed. Detail analysis of the capacitive coupling signals and its performance in both time and frequency domains were discussed. The proposed pointing device was build and implemented. Experimental results show potential for commercialization of the wireless-pointing device and its robustness.